2019
DOI: 10.1016/j.colsurfa.2019.123676
|View full text |Cite
|
Sign up to set email alerts
|

Investigating chromatographic interactions in porous pigment coatings between inkjettable polyelectrolytes and model colorant solutions

Abstract: Printed, self-contained sensor designs based on capillary transport and microfluidic principles form a major part of current research in printed functionality. Previous work into such designs has mainly focused on cellulosic papers as base substrates. In this study, novel findings are presented employing alternative customdesigned functional pigment coated substrates, locally functionalised by inkjet printed polyelectrolytes, to separate or transport anionic or cationic molecules by surface chemistry tailoring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…Figure f shows the extracted retardation factor R f as a function of c 0 . The results qualitatively resemble those obtained by Koivunen et al using the imbibition of tartrazine and safranine solutions from infinite reservoirs into porous layers that are comprised of calcium carbonate microparticles and polymeric binders …”
Section: Results and Discussionsupporting
confidence: 86%
“…Figure f shows the extracted retardation factor R f as a function of c 0 . The results qualitatively resemble those obtained by Koivunen et al using the imbibition of tartrazine and safranine solutions from infinite reservoirs into porous layers that are comprised of calcium carbonate microparticles and polymeric binders …”
Section: Results and Discussionsupporting
confidence: 86%
“…Furthermore, we have shown that our coatings are biocompatible and that they offer enhanced sensitivity compared to filter paper (Jutila et al 2019). We have also shown that the properties of the coating can be altered either completely (Jutila et al 2019) or locally (Koivunen et al 2017(Koivunen et al , 2019 with polyelectrolytes, affecting the transfer and separation of positively or negatively charged molecules on the coating, which may be useful for some microfluidic applications.…”
Section: Introductionmentioning
confidence: 81%
“…Hydrophobising ink consisted of 10 w/w% commercial AKD FennoWax 1865 (Kemira, Helsinki, Finland) dissolved in p-xylene. Jetting settings were as described previously by the authors for a similar, though colourant containing, ink in contemporary work (Koivunen et al 2019). The hydrophobising ink in the present case contains no colourant, resulting in almost invisible printed patterns for minimum background interference in the colorimetric analysis.…”
Section: Printing Of Hydrophobic Patterningmentioning
confidence: 99%
See 2 more Smart Citations